KEMAMPUAN MENULIS TEKS PROSEDUR DALAM KEGIATAN PEMBELAJARAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) SISWA KELAS VII SMPN 4 KUBUNG KABUPATEN SOLOK - Latifa, Syima; Putri, Mega; Wirasty B., Rini (JELISA (Jurnal Edukasi dan Literasi Bahasa), 2024)
This research was motivated by students' ability to write procedural texts in learning activities (P5). Based on the results of observations and interviews that researchers found, in the P5 learning activity report there are procedures or procedures for working on a project. Therefore, researchers found a connection between learning Indonesian, namely procedural texts in making reports from P5 activities. This type of research is quantitative using descriptive research methods. This research data was obtained from the results of student performance. The data collection techniques in this research are: (1) the researcher explains writing procedural texts based on their structure and linguistic characteristics to students. (2) the researcher provides examples of correct procedural texts according to their structure and linguistic characteristics. (3) the researcher gives students the opportunity to ask questions about the procedure text that will be written. (4) the researcher instructed the students to write procedure texts according to what had been practiced in the P5 local wisdom activity "making batik" (5) the researcher collected the students' procedure texts that had been written. Based on the research results, it was found that the ability to write procedure texts in P5 learning according to the procedure text structure was 93.35 with very good qualifications and linguistic rules were 83.9 with good qualifications. Based on the research results described in chapter IV, the ability to write procedural texts in learning activities (P5), class VII students at SMPN 4 Kubung, Solok Regency obtained an average of 88.67 with excellent qualifications.